2013
DOI: 10.1002/jbm.b.33087
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteoconductivity of sodium‐substituted hydroxyapatite by system instability

Abstract: The effect of substituting sodium for calcium on enhanced osteoconductivity of hydroxyapatite was newly investigated. Sodium-substituted hydroxyapatite was synthesized by reacting calcium hydroxide and phosphoric acid with sodium nitrate followed by sintering. As a control, pure hydroxyapatite was prepared under identical conditions, but without the addition of sodium nitrate. Substitution of calcium with sodium in hydroxyapatite produced the structural vacancies for carbonate ion from phosphate site and hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 94 publications
(164 reference statements)
4
23
0
Order By: Relevance
“…When the Na concentration in the treatment solutions increased, the formation of HA as a residual material was inhibited. Additionally, as reported by Sang Cho et al () Na‐substituted HA exhibited higher osteoconductivity compared to nonsubstituted HA in vivo.…”
Section: Discussionsupporting
confidence: 67%
“…When the Na concentration in the treatment solutions increased, the formation of HA as a residual material was inhibited. Additionally, as reported by Sang Cho et al () Na‐substituted HA exhibited higher osteoconductivity compared to nonsubstituted HA in vivo.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, anionic dopants such as by F − , Cl − , CO 3 − , PO 4 3− , and CO 3 2− replace OH − . Sang Cho et al reported that Na‐HA improves osteoconductivity in rabbits due to enhanced dissolution of HA at the bone interface leading to better bioactivity compared to undoped HA. Bose et al reported that Mg doped HA (Mg‐HA) affects osteoblasts’ activity and accelerates bone ingrowth in to these doped HA implants.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (HAP), the chemically pure version of the mineral component of bone, however, is typified by impractically low resorption rates [13]. Reduction of the particle size [4], an increase in porosity [5] and introduction of ionic substitutions, such as magnesium [6], sodium [7], fluorine [8] and/or carbonate [9], so as to mimic the composition and microstructure of biological apatite, have presented approaches to resolving this issue, though with limited success. Namely, even the least sparingly soluble calcium-deficient apatites usually resorb slower than the new bone tissue formation rate [10], whereas HAP with high porosity is weak even to compression and not suitable for load-bearing applications [11].…”
Section: Introductionmentioning
confidence: 99%